2013
DOI: 10.1097/mib.0b013e31829ed855
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Anemia in Pediatric Inflammatory Bowel Disease

Abstract: Anemia is high at diagnosis and follow-up and should receive more attention from the clinical team; however, the focus should remain suppression of inflammatory process in active disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…However, there was no such a significant difference in serum levels of vitamin B12, folic acid, ferritin and transferrin between IBD patients and healthy controls ( P > 0.05). These results indicate that the majority of IBD patients with anemia suffer from serum iron deficiency, consistent with previous reports 7 8 9 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, there was no such a significant difference in serum levels of vitamin B12, folic acid, ferritin and transferrin between IBD patients and healthy controls ( P > 0.05). These results indicate that the majority of IBD patients with anemia suffer from serum iron deficiency, consistent with previous reports 7 8 9 .…”
Section: Resultssupporting
confidence: 93%
“…Anemia in IBD patients may result from several causes such as lack of iron and other chronic diseases. Some patients are also caused by loss of vitamin B12 and folate, drug-associated side-effects (e.g., sulfasalazine, thiopurine) and several hematologic diseases 7 8 9 . Consistent with these findings, intravenous iron therapy has been performed in the treatment of anemia in patients with IBD and proven to be effective in the clinic 10 .…”
mentioning
confidence: 99%
“…Previously reported data from smaller studies have shown similar prevalence of anemia with 70% in children and 42% in adolescents compared to 40% in adults [ 9 , 16 ].…”
Section: Discussionmentioning
confidence: 89%
“…We found in our study that almost two-thirds of pediatric IBD patients were anemic at the time of diagnosis. So far, there are very few studies that aim at anemia and iron deficiency in pediatric IBD, most of them in rather small cohorts and with short follow-up [ 8 , 9 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation